2019
DOI: 10.1186/s12903-019-0931-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between gingival parameters and Oral health–related quality of life in Caribbean adults: a population-based cross-sectional study

Abstract: BackgroundGood oral health has been associated with better quality of life and general health. In the Caribbean, there have been no studies regarding the association between oral health conditions and the quality of life of the population. The main purpose of this study was to investigate the association between gingival parameters and oral health–related quality of life (OHRQoL) in Caribbean adults. A secondary aim of the study was to gain more information on factors that impact OHRQoL in this population.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
16
1
1
Order By: Relevance
“…Additionally, it is well established that smokers tend to have a worse perception of their oral health when compared to non-smokers. Likewise, smokers are also inclined to have a greater impact of OHRQoL 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is well established that smokers tend to have a worse perception of their oral health when compared to non-smokers. Likewise, smokers are also inclined to have a greater impact of OHRQoL 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies on the potential determinants of OHRQoL mainly addressed the clinical, socioeconomic, and demographic characteristics, which may explain only part of the variation of the OHRQoL. [ 3 4 5 6 ] However, a growing interest directed toward the roles of psychosocial factors as determinants of OHRQoL. [ 7 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple studies in different populations which have shown the association of sociodemographic factors, general health status and oral health conditions and their impact in OHRQoL. 1,2,4,[6][7][8][9][10] However, there is very little information regarding the impact of oral health and OHRQoL in Jamaica and the Caribbean region. Collins et al, in a multicentre study done in three Caribbean cities (Kingston, Jamaica; Santo Domingo, Dominican Republic and San Juan, Puerto Rico), showed that factors such as gingival health, smoking, frequency of dental visits and the presence of chronic diseases impacted the OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Collins et al, in a multicentre study done in three Caribbean cities (Kingston, Jamaica; Santo Domingo, Dominican Republic and San Juan, Puerto Rico), showed that factors such as gingival health, smoking, frequency of dental visits and the presence of chronic diseases impacted the OHRQoL. 10 Notwithstanding this publication, more studies are needed in Jamaica and the Caribbean region to ascertain information about oral health status, including decayed, missing and filled teeth (DMFT) and its impact on OHRQoL. With this background, the aim of this cross-sectional study was to evaluate the impact of sociodemographic characteristics, oral health status and behaviours of adult Jamaican population on their OHRQoL.…”
Section: Introductionmentioning
confidence: 99%